2016
DOI: 10.1080/0886022x.2016.1227921
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in morphology and hepatorenal indices in rats subacutely exposed to bitumen extract

Abstract: Bitumen is a complex mixture of dense and extremely viscous organic liquids produced by distillation of crude oil during petroleum refining. Nigeria has a large deposit of natural bitumen, yet to be fully exploited. Discharges of petroleum hydrocarbons and other petroleum-derived products have caused environmental pollution and adverse human health effects in several oil-rich communities. In this study, bitumen obtained from a seepage source in Agbabu, the town of first discovery, was used in sub-acute toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…One of the findings of the present study is the significant elevation of AST enzyme in the asphalt-exposed group compared to the control group. Just like in our study, previous works confirmed the significant elevation of AST activity in rats exposed to bitumen extract [3]. AST is found in the mitochondria of liver, kidney, and heart cells.…”
Section: The Toxicity Of Chemical Compounds Is Estimated Biochemically By the Tracking Of Plasma Lipids And Enzymessupporting
confidence: 92%
See 3 more Smart Citations
“…One of the findings of the present study is the significant elevation of AST enzyme in the asphalt-exposed group compared to the control group. Just like in our study, previous works confirmed the significant elevation of AST activity in rats exposed to bitumen extract [3]. AST is found in the mitochondria of liver, kidney, and heart cells.…”
Section: The Toxicity Of Chemical Compounds Is Estimated Biochemically By the Tracking Of Plasma Lipids And Enzymessupporting
confidence: 92%
“…Previous studies confirmed that hepatotoxicity in the experimental rat model could be assessed by plasma triglyceride assay. Otuechere et al had already reported a similar finding of an increased level of triglyceride in an experimental rat model exposed to bitumen extract [3]. Contrary to our findings, decreased levels of AST and ALT were reported for those subjects occupationally exposed to petroleum oil [28].…”
Section: The Toxicity Of Chemical Compounds Is Estimated Biochemically By the Tracking Of Plasma Lipids And Enzymescontrasting
confidence: 67%
See 2 more Smart Citations